Study on the effects of spermidine on LPS-induced inflammatory osteolysis in mouse calvaria - ZHAO Xinyu; ZHANG Wenchao; CHEN Xuzhuo; SONG Jiaqi; HUANG Hui; ZHANG Shanyong (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2025)
Objective·To investigate the inhibitory effects of spermidine (SPD) on inflammatory osteolysis both in vivo and in vitro.Methods·The CCK-8 assay was used to assess the viability of RAW264.7 macrophages treated with various concentrations of SPD. The levels of intracellular reactive oxygen species (ROS) in lipopolysaccharide (LPS)-activated RAW264.7 cells were evaluated by staining with dichlorodihydrofluorescein diacetate (DCFH-DA) and dihydroethidium (DHE), respectively. Reverse transcription real-time fluorescence quantitative PCR (RT-qPCR) was utilized to determine the effects of SPD on the expression of pro-inflammatory genes in LPS-activated RAW264.7 cells. Tartrate-resistant acid phosphatase (TRAP) staining was used to evaluate the effect of SPD on the differentiation of mouse primary bone marrow-derived macrophages (BMMs) into osteoclasts. RT-qPCR was employed to further analyze the effect of SPD on the expression of genes related to osteoclast differentiation and functions after BMM-induced differentiation. An LPS-induced mouse calvarial osteolysis model was constructed, and the therapeutic efficacy of SPD on inflammatory osteolysis was assessed using Micro-CT analysis, hematoxylin-eosin (H-E) staining and TRAP staining of histological sections.Results·The CCK-8 assay showed that SPD, even at a concentration of 1 000 μmol/L, exhibited no significant cytotoxicity to RAW264.7 cells. ROS analysis revealed that SPD markedly inhibited LPS-induced elevation of intracellular ROS levels in macrophages. RT-qPCR results indicated that SPD suppressed the expression of pro-inflammatory genes induced by LPS. Both TRAP staining and RT-qPCR demonstrated that SPD effectively inhibited the differentiation of BMMs into osteoclasts induced by receptor activator of nuclear factor-κB ligand (RANKL) and reduced the expression of genes associated with osteoclast differentiation and function. In the mouse calvarial osteolysis model, Micro-CT analysis showed that the bone volume fraction and bone mineral density in the SPD-treated groups were significantly higher than those in the LPS group. Histological staining revealed that SPD treatment reduced inflammatory cell infiltration, decreased osteoclast numbers, and alleviated tissue damage.Conclusion·SPD inhibits macrophage inflammatory responses and RANKL-induced osteoclast differentiation in vitro; in vivo, it alleviates LPS-induced inflammatory calvarial osteolysis in mice.